Theory of Substantivity: A Necessary Expansion of the Theory of Substance - Beites, Pilar Fernández (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This article aims to expound the ontological theory of Xavier Zubiri in order to come up with a «theory of substantivity» capable of incorporating the classical theory of substance. An even more fundamental difference than classical theory’s distinction between substance and accidents is the distinction between whole and parts: the independent or autonomous parts that structure the real are not principally «substances» but «substantivities» or wholes. But defending a theory of substantivity does not presuppose rejecting the theory of substance. In the theory of substantivity, substance continues to play an important ontological role for two reasons. First, because we cannot descriptively do away with the substance-accident relation: a substantivity has to be considered a substance (not in the strictsense) insofar as it supports accidents and the same is true with the «independent parts», since their independence is precisely the expression of their substantiality. Second, we cannot give up the theory of substance because we have to admit at least the existence of a substance in the strict sense, of a simple substance (simplicity in the strict sense), which is the «I» as pure subject (the «soul» of classical theory). And it is at this point that the article definitely distances itself from the later Zubiri.